Utvärdering av olika diagnostiska metoder för infektioner med bovint coronavirus hos nötkreatur - Svensson, Daniel (2005)
This paper shortly describes the coronavirus family, bovine corona viruses (BCV) properties and two diseases that BCV causes, winter dysentery and calf diarrhoea. The purpose of the study was to compare different diagnostic methods to detect BCV. Different methods are discussed, PCR, ELISA, immunofluorescense and virus isolation. Investigations were made in three different herds with winter dysentery; one dairy cattle farm with about 100 cows of different ages, one testing station for bulls with about 150 bulls and another small dairy cattle farm with 26 cows and 20 replacement heifers and calves. Faeces and nasal swabs were analysed with PCR and ELISA. The result shows that PCR seems to be a reliable method for detecting BCV but that the ELISA test can not be used as a reliable diagnostic method to analyse samples from animals with winter dysentery.